Manajemen Penyidikan Dalam Penanganan Kasus Hukum Pidana Di Direktorat Reserse Kriminal Umum Polda Kalimantan Selatan - Muhammad Arif; Singgih Priono (STIA Bina Banua Banjarmasin, 2019)
The purpose of this study is to describe and analyze the management process of criminal investigations carried out by investigators and assistant investigators in the Directorate of Criminal Investigation of South Kalimantan Police. This study uses qualitative research methods using interview and documentation data collection techniques. From the data obtained that investigators in the Directorate General of Criminal Investigation of South Kalimantan Regional Police numbered 22 people, around 72% with the latest education undergraduate and dikjur. Assistant investigators numbered 57 people and about 47% with the latest undergraduate education. The results of this study are that an investigation conducted by an investigator who does not yet have a strata 1 education turns out to have an impact on whether or not the investigation process is carried out in handling a criminal case. The success of the case disclosure and handling the investigation process of a criminal act until the trial, can not be separated from how to plan, organize, implement and supervise properly so that the target of crime clearing is in line with what is expected. Tujuan penelitian ini adalah untuk mendiskripsikan dan menganalisis proses manajemen penyidikan tindak pidana yang dilakukan oleh penyidik dan penyidik pembantu di Direktorat Reserse Kriminal Umum Polda Kalsel. Penelitian ini menggunakan metode penelitian kualitatif dengan menggunakan teknik pengumpulan data wawancara dan dokumentasi. Dari data yang didapatkan bahwa penyidik di Direktorat Reserse Kriminal Umum Polda Kalsel berjumlah 22 orang sekitar 72% dengan pendidikan terakhir sarjana dan dikjur. Penyidik pembantu berjumlah 57 orang dan sekitar 47% dengan pendidikan terakhir sarjana. Hasil dari penelitian ini adalah Penyidikan yang dilakukan oleh seorang penyidik yang belum memiliki pendidikan strata 1 ternyata berdampak pada sah atau tidaknya proses penyidikan yang dilakukan dalam penanganan suatu kasus pidana. Keberhasilan pengungkapan kasus dan penanganan proses penyidikan suatu tindak pidana sampai kepersidangan, tidak lepas dari bagaimana melakukan perencanaan, pengorganisasian, pelaksanaan dan pengawasan yang baik sehingga target crime clearing sesuai apa yang diharapkan.